UPDATE ON ALOCASIA CUPREA K.KOCH DISTRIBUTION IN NORTH KALIMANTAN - Ni Putu Sri Asih; Dewi - Lestari (Reinwardtia, 2022)
ASIH, N. P. S. & LESTARI, D. 2022. Update on Alocasia cuprea K.Koch distribution in North Kalimantan. Reinwardtia 21(2): 49‒53. — Hitherto Malaysian Bornean Alocasia cuprea K.Koch is a newly recorded species for North Kalimantan, taking Alocasia in Kalimantan to 10 species. An identification key and photos of A. cuprea are presented